Discovery of potential ferroptosis and osteoporosis biomarkers through TMT proteomics and bioinformatics analysis - Hui Su; Guoqing Tan; WenXuan Guo; Jin Sheng Yu; Zhanwang Xu; RuJie Zhuang; Haipeng Xue (BioMedical Engineering OnLine)
Abstract Background Primary osteoporosis has increasingly emerged as a major issue affecting human health, with a complex specific pathogenic mechanism. As a research hotspot, ferroptosis plays a vital role in the pathogenesis of primary osteoporosis, aiming to explore the link and specific target genes between ferroptosis and primary osteoporosis. Methods By utilizing TMT proteomics and bioinformatics analyses, we elucidated the linkages and key targets of the ferroptosis pathway in an ovariectomized osteoporotic rat model. Forty 12-week-old SD female rats were employed in the study, of which 20 female SD rats were ovariectomized as the OVX group and 20 female SD rats were employed as the SHAM group. At the end of the experiments, the femurs of the rats were excised for computed tomography tests and used for hematoxylin and eosin staining. Finally, we extracted bone tissue proteins for TMT proteomics analysis and protein blotting verification. Results The proteomics results of the VX and SHAM groups showed that 133 proteins were significantly changed, of which 91 proteins were upregulated and 42 proteins were downregulated, including TXN, TMSB4X, TFRC, TF, RELA, PARP14, CP, CAPG, and ADIPOQ. The expression of key proteins in the bone tissues was detected by protein blotting. The expression of TFR1, TFRC and TF was upregulated, whereas the expression of Cp, TXN and BMP-2 was downregulated. Conclusions TMT proteomics and functional enrichment analyses in our study substantiated that in osteoporosis, disturbances in lipid metabolism lead to the emergence of oxidative stress with iron homeostasis imbalance.